Use of “Glass Curtain” Systems to Improve the Energy Efficiency and Thermal Comfort of Dwellings in a Warm Semi-Arid Mediterranean Climate - Carlos Pérez-Carramiñana; Samuel Sabatell-Canales; Ángel Benigno González-Avilés; Antonio Galiano-Garrigós (Applied Sciences, 2023)
The dry Mediterranean climate (BShs) within a warm semi-arid climate (BSh) is the zone in Europe with the most annual hours of sunlight, and it has a smaller annual temperature variation than most climates. This allows the greenhouse effect caused by windows to be used to heat dwellings in winter. Balcony frameless retractable glazing systems known as “glass curtain” systems offer the highest proportion of glass and maximum openness in the façade, allowing for maximum sunlight and ventilation. This work studies a glazed terrace with a “glass curtain” in a dwelling on the Spanish Mediterranean coastline. The objective is to quantitatively determine the enhancement of the thermal comfort and energy efficiency of a dwelling using “glass curtain” systems. The modification of several design parameters of the glazed terrace is also analysed. The novelty of this study lies in demonstrating that the use and optimised design of “glass curtain” systems allows us to obtain nearly zero-energy buildings (nZEBs) and thermally comfortable dwellings all year round. The research methods include a comparison of the current thermal performance of the dwelling with and without a “glass curtain” system via on-site measurements. The study also evaluates the influence of modifying design parameters using computer simulations. The results show that “glass curtain” systems increase the indoor temperatures inside the dwelling by about 4 °C in winter and reduce the annual indoor thermal oscillation from more than 16 °C to only 10 °C. Consequently, such systems reduce heating energy needs by almost 60%. Glazed terraces using the proposed design parameters show further improvement regarding thermal comfort and practically eliminate heating and cooling needs.